Design considerations for future affective automotive interfaces: a review of self-regulation strategies to manage affect behind the wheel - Lohani, Monika; Do, Amy S.; Aisa, Aifara (Frontiers in Future Transportation, 2024)
Like inattention, dysregulated emotions can seriously distract motorists and disrupt their driving performance. The current review examined the literature on emotion regulation to find relevant strategies for managing intense emotions while driving a motor vehicle. Next, we considered whether those relevant strategies could be used to design future affective automotive interfaces. Results suggested that problem-solving, task-focused coping, mindfulness, acceptance, and relaxation effectively regulate emotions while driving. These findings highlight that some strategies may be effective but costly to implement while driving (cognitive reappraisal and distraction), which need to be better understood before implementing them into automotive interfaces. Together, these findings suggest the potential benefits of embedding self-regulatory interventions in future automotive interfaces that can help maintain an optimal affective state to reduce distraction and improve safe driving.